2015
DOI: 10.1007/s11908-015-0484-7
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and Treatment of Trichomoniasis

Abstract: Trichomonas vaginalis is the most common nonviral sexually transmitted infection (STI) in the world. It was once thought to be a nuisance STI, but it is now being recognized as an important source of reproductive morbidity and a facilitator of HIV transmission and acquisition, and thus it is an important public health problem. The prevalence of T. vaginalis varies greatly by geography and risk group, but is more common among persons of African descent and appears to increase with age, though this may be a scre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
71
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(74 citation statements)
references
References 108 publications
(122 reference statements)
0
71
1
Order By: Relevance
“…vaginalis isolates have occurred in recent years, supporting the evidence that resistance is on the rise (Klebanoff et al, 2001;Schwebke and Barrientes, 2006;Miller and Nyirjesy, 2011;Kissinger, 2015). Though the mechanism of metronidazole resistance in T. vaginalis from treatment failures is not well understood, one hypothesis is that the resistance of T. vaginalis to metronidazole occurs through several stages based on the significant reduction and eventual loss of activity of ferredoxin and pyruvate:ferredoxin oxidoreductase (PFOR), two enzymes involved in drug activation.…”
Section: Introductionmentioning
confidence: 91%
“…vaginalis isolates have occurred in recent years, supporting the evidence that resistance is on the rise (Klebanoff et al, 2001;Schwebke and Barrientes, 2006;Miller and Nyirjesy, 2011;Kissinger, 2015). Though the mechanism of metronidazole resistance in T. vaginalis from treatment failures is not well understood, one hypothesis is that the resistance of T. vaginalis to metronidazole occurs through several stages based on the significant reduction and eventual loss of activity of ferredoxin and pyruvate:ferredoxin oxidoreductase (PFOR), two enzymes involved in drug activation.…”
Section: Introductionmentioning
confidence: 91%
“…These estimates are population dependent, with very high rates among some groups and almost no disease in others. In Europe, recent population level studies have estimated the prevalence of disease to be Ͻ1% in countries with chlamydia rates similar to those in the United States, suggesting a geographic fluctuation in the underlying presence of disease that is not well described or understood (5). In the United States, geographic fluctuation of rates is observed, but the ratio of trichomonas to chlamydia infections remains similar (6).…”
mentioning
confidence: 99%
“…Research studies of men with NGU suggest that T. vaginalis is responsible for 10 to 12% of these cases of urethritis (11), one of the most common reasons why men Ͻ50 years old seek health care. Certain high-risk populations may warrant routine screening, such as women attending STD clinics, women in correctional facilities, women living in high-prevalence regions, men with urethritis, and sexual partners of infected women (4,5,12). However, programmatic decisions to offer screening should be based on local epidemiologic data whenever possible.…”
mentioning
confidence: 99%
“…15 Although research has indicated that effective T. vaginalis control may reduce HIV transmission and acquisition, 16 the infection is asymptomatic in the majority of cases, 17 so it is rarely screened for and often remains untreated. 18 …”
Section: Introductionmentioning
confidence: 99%
“…19 Another study found that black women had T. vaginalis rates that were ten times higher than white women, constituting a significant health disparity. 17 Unlike other STIs, T. vaginalis infection disproportionately affects older women, 18 who are also overrepresented in the criminal justice system. A national profile shows that women in the criminal justice system are typically in their early to mid-thirties.…”
Section: Introductionmentioning
confidence: 99%